2017
DOI: 10.3847/2041-8213/aa6c2d
|View full text |Cite
|
Sign up to set email alerts
|

High Radiation Pressure on Interstellar Dust Computed by Light-scattering Simulation on Fluffy Agglomerates of Magnesium-silicate Grains with Metallic-iron Inclusions

Abstract: Recent space missions have provided information on the physical and chemical properties of interstellar grains such as the ratio β of radiation pressure to gravity acting on the grains in addition to the composition, structure, and size distribution of the grains. Numerical simulation on the trajectories of interstellar grains captured by Stardust and returned to Earth constrained the β ratio for the Stardust samples of interstellar origin. However, recent accurate calculations of radiation pressure cross-sect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The Stardust particles also showed that interstellar dust with mass 3 · 10 −15 kg might be porous and has higher β and charge-to-mass ratios . Interstellar dust with mass exceeding 5 · 10 −16 kg might be porous aggregates of submicron-sized silicate grains Kimura, 2017). Silicate grains do not stick to each other in the interstellar medium, but organic matter would assist them in sticking, if their surfaces are covered by organic matter.…”
Section: Interstellar Dustmentioning
confidence: 99%
“…The Stardust particles also showed that interstellar dust with mass 3 · 10 −15 kg might be porous and has higher β and charge-to-mass ratios . Interstellar dust with mass exceeding 5 · 10 −16 kg might be porous aggregates of submicron-sized silicate grains Kimura, 2017). Silicate grains do not stick to each other in the interstellar medium, but organic matter would assist them in sticking, if their surfaces are covered by organic matter.…”
Section: Interstellar Dustmentioning
confidence: 99%
“…1 of Ferrara et al (1991), indicating that a higher value up to q = 2.5 could be appropriate for minor graphite grains. Similarly, if the grains have a composite fluffy character, as suggested by Kimura (2017) on the basis of captured Local Interstellar Cloud grains, an increase of q by up to a factor of two may be adequate for the more massive particles. The speed of light is c and Newton's constant of gravity is G. The dust grain is retarded by a drag force, described by the last term of the right-hand side of Eq.…”
Section: The Model and The Resultsmentioning
confidence: 96%
“…For the relevant dust and stellar light discussed here a mean q pr ≡ q of about 1.5 may be adopted, see, however, Fig 1 of Ferrara et al (1991), indicating that a higher value up to q = 2.5 could be appropriate for minor graphite grains. Similarly, if the grains have a composite fluffy character, as suggested by Kimura (2017) on the basis of captured Local Interstellar Cloud grains, an increase of q by up to a factor of two may be adequate for the more massive particles. The speed of light is c and Newton's constant of gravity is G. The dust grain is retarded by a drag force, described by the last term of the right-hand side of Equation ( 1).…”
Section: The Model and The Resultsmentioning
confidence: 96%